El concepto de número: repensando la organización de la enseñanza - Edilson de Araújo dos Santos; Luciana Figueiredo Lacanallo Arrais (Universidade Federal de Rondônia, 2019)
This paper aims to present reflections on the didactic tools used to teach the number in the first year of schooling, pointing out its limits and listing possibilities. In this sense, we performed a field research that is exposed as follows: initially we discussed the research done on the instruments and methodological referrals for number teaching, these data were obtained through a data collection during the first semester of the school year of 2017 at a school in the northern region of Paraná. Having verified the school practices, we resort to the study on the origin of numbers, from which we seek to understand the need to create this concept. Finally, we present some elements of teaching the concept of number according to the principles of davydovians, among which we chose the numerical line as a didactic possibility. We hope that this work contributes to thinking about the organization of Mathematics teaching in the initial years of Elementary School.